(untitled) (Fiep Bulletin - online, 2012)
The International Physical Education Federation (IPEF) history in Uruguay began with Prof. Alberto Langlade when returning of the "II Linghíada" in 1949, he was appointed as IPEF Delegate for Uruguay, a position he held until 1980, when he died at 59 years of age. His career was brilliant; his books were distributed around the world and were used as textbooks in schools and institutes of physical education.